Pra-Rancangan Pabrik Fatty Alcohol dari Kelapa Sawit dengan Transesterifikasi Metanol Kapasitas 70.000 Ton/Tahun - Eigiya Nina Tarigan (Fakultas Teknik, 2025)
A palm oil-based fatty alcohol plant using methanol transesterification is designed to produce 70,000 tons of product per year. The oleochemical industry, especially palm oil-based, is growing rapidly due to the abundance and environmental friendliness of palm oil as a raw material. This plant is expected to reduce Indonesia's dependence on imported raw materials and meet the growing domestic and export demand for fatty alcohol. Indonesia, as the leading producer of palm oil, has great potential in the development of the fatty alcohol industry. With the utilization of abundant palm oil, this plant will strengthen the renewable resource-based industrial sector. Fatty alcohol production uses a methanol transesterification process that provides high yields and is environmentally friendly. The plant is planned to be built in Medan, North Sumatra, with a production capacity of 70,000 tons per year, utilizing 560,240,000 tons of palm oil annually. In the design of this plant, various production stages, including hydrogenation and purification, are carried out with a capacity of 8,838.4 kg of fatty alcohol per hour to achieve a purity of 98% for the final product and glycerol with a purity of 81.5% as a by-product. In the preliminary design of this plant, fatty alcohol is produced through three process stages: pretreatment, transesterification, and hydrogenation. The plant's utilities include the supply of water, steam, electricity, fuel, and waste treatment. The planned company structure for this preliminary design of the fatty alcohol plant is a Limited Liability Company (PT) with a line and staff organizational structure. The number of employees required is 188. The economic evaluation analysis indicates that the project is feasible with a Payback Period (POT) of 2.06 years and a Break-Even Point (BEP) of 41.17%. Therefore, the establishment of this fatty alcohol plant is expected to reduce Indonesia's dependence on imported fatty alcohol and meet the needs of other industries.
Reupload Repository Mei 2026 :: Finalisasi Repositori File 19 Mei 2026_Kurnadi
Keywords: Fatty Alcohol; Kelapa Sawit; Metanol